Changes in valve morphology of two pennate diatom species during long-term culture - Petrova, Darya P.; Bedoshvili, Yekaterina D.; Zakharova, Yulia R.; Volokitina, Nadejda A.; Likhoshway, Yelena V.; Grachev, Michael A. (Acta Biologica Sibirica, 2020)
The morphology of diatom siliceous is a primary basis for their species identification. This study aims to measure the range of morphological changes induced in the monoclonal cultures of Fragilaria radians strains 280 and A6 and Ulnaria danica strain BK17 by cultivation in the lab for a year or more. The scanning electron microscopy revealed that the number of abnormal valves increases during the first year of culture maintenance. Specific abnormalities observed include curved valves and apices, axial areas and rimoportulae shifted from their normal positions, disordered or otherwise abnormal striae, and various growths on the valves. Similar morphological abnormalities are known to occur in diatoms exposed to microtubule inhibitors. These results show the limits of morphological variance in studied species and could be used to estimate the effect of toxic agents in natural and experimental conditions.